Lipoprotein apheresis affects lipoprotein particle subclasses more efficiently compared to the PCSK9 inhibitor evolocumab, a pilot study. Issue 1 (February 2018) - Lappegård, Knut Tore; Kjellmo, Christian Abendstein; Ljunggren, Stefan; Cederbrant, Karin; Marcusson-Ståhl, Maritha; Mathisen, Monica; Karlsson, Helen; Hovland, Anders
Abstract: Lipoprotein apheresis and proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors are last therapeutic resorts in patients with familial hypercholesterolemia (FH). We explored changes in lipoprotein subclasses and high-density lipoprotein (HDL) function when changing treatment from lipoprotein apheresis to PCSK9 inhibition. We measured the levels of low-density lipoprotein (LDL) and HDL particle subclasses, serum amyloid A1 (SAA1), paraoxonase-1 (PON1) activity and cholesterol efflux capacity (CEC) in three heterozygous FH patients. Concentrations of all LDL particle subclasses were reduced during apheresis (large 68.0 ± 17.5 to 16.3 ± 2.1 mg/dL, (p = 0.03), intermediate 38.3 ± 0.6 to 5.0 ± 3.5 mg/dL (p = 0.004) and small 5.0 ± 2.6 to 0.2 ± 0.1 mg/dL (p = 0.08)). There were non-significant reductions in the LDL subclasses during evolocumab treatment. There were non-significant reductions in subclasses of HDL particles during apheresis, and no changes during evolocumab treatment. CEC was unchanged throughout the study, while the SAA1/PON1 ratio was unchanged during apheresis but decreased during evolocumab treatment. In conclusion, there were significant reductions in large and intermediate size LDL particles during apheresis, and a non-significant reduction in small LDL particles. There were only non-significant reductions in the LDL subclasses during evolocumab treatment.